2018
DOI: 10.1111/age.12675
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the blood transcriptomes between wolves and dogs

Abstract: Dogs were domesticated by human and originated from wolves. Their evolutionary relationships have attracted much scientific interest due to their genetic affinity but different habitats. To identify the differences between dogs and wolves associated with domestication, we analysed the blood transcriptomes of wolves and dogs by RNA-Seq. We obtained a total of 30.87 Gb of raw reads from two dogs and three wolves using RNA-Seq technology. Comparisons of the wolf and dog transcriptomes revealed 524 genes different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 46 publications
2
45
0
Order By: Relevance
“…Similar results have been found in tomato (Koenig et al, 2013), pea (Hradilová et al, 2017), common bean (Singh et al, 2018), and carrot (Machaj et al, 2018). This approach has also led to the discovery of differentially expressed genes between dogs and wolves associated to tameness (Li et al, 2013), as well as changes related to the immune system and aerobic capacity (Yang et al, 2018). Another study found differential isoform expression between wild and domesticated sorghum accessions, revealing that domestication can alter the patterns of alternative spicing (Ranwez et al, 2017).…”
Section: Successful Examples Of Rna-seq Experiments To Understand Domsupporting
confidence: 60%
“…Similar results have been found in tomato (Koenig et al, 2013), pea (Hradilová et al, 2017), common bean (Singh et al, 2018), and carrot (Machaj et al, 2018). This approach has also led to the discovery of differentially expressed genes between dogs and wolves associated to tameness (Li et al, 2013), as well as changes related to the immune system and aerobic capacity (Yang et al, 2018). Another study found differential isoform expression between wild and domesticated sorghum accessions, revealing that domestication can alter the patterns of alternative spicing (Ranwez et al, 2017).…”
Section: Successful Examples Of Rna-seq Experiments To Understand Domsupporting
confidence: 60%
“…Similar to our findings, the identified GO terms largely belonged to a broad spectrum of biological processes such as immunity, development, reproduction and metabolism, as well as cellular processes such as cell adhesion, cell–cell interaction, motility and signal transduction. Comparably, the immune‐related processes were enriched in the comparison of frontal cortex transcriptomes of wild boar and domestic pig in a study by Long et al and in a study of blood transcriptomes between wolves and dogs . The comparative studies of transcriptomes from thalamus/hypothalamus of wild Red Junglefowl and Red Junglefowl selected for tameness for five generations largely identified genes related to spermatogenesis and immunity, but the comparative analysis of cerebral hemisphere transcriptomes in these populations suggested an enrichment for genes associated with behavioral processes .…”
Section: Discussionmentioning
confidence: 98%
“…This could be due to the area of the hypothalamus sampled, as we did not selectively screen the para- Long et al 123 and in a study of blood transcriptomes between wolves and dogs. 124 The comparative studies of transcriptomes from thalamus/hypothalamus of wild Red Junglefowl and Red Junglefowl selected for tameness for five generations largely identified genes related to spermatogenesis and immunity, 21 but the comparative analysis of cerebral hemisphere transcriptomes in these populations suggested an enrichment for genes associated with behavioral processes. 125 Furthermore, genes that were DE between the two groups Comparison of hypothalamus DEGs with the gene content of genomic regions differentiating fox populations 36 identified 10 genes in common.…”
Section: F I G U R Ementioning
confidence: 99%
“…Moreover, in many human diseases, aggressiveness can be a risk factor (e.g., [20]), a symptom (e.g., [21]), or a complication of treatment (e.g., [22]). On a whole-genome scale, many animals are already subjected to aggressiveness studies, including the trout [23], chickens [24], foxes [25,26], dogs [27,28], pigs [29,30], rats [29,31], mice [32], rabbits, and guinea pigs [29]; however, this research still does not take into account the reference human genome [33], human variome [34], or the classification of diseases and health problems ICD-11 [35].…”
Section: Introductionmentioning
confidence: 99%